'Sizzle' and 'Passionista'—Two Lance-Leaved Caladium Cultivars - Zhanao Deng (EDIS)
Many lance-leaved cultivars often produce small tubers, making it difficult for growers to produce tubers profitably. ‘Sizzle’ and ‘Passionista’ are two new lance-leaved caladium cultivars with improved tuber yield potential. The availability of ‘Sizzle’ and ‘Passionista’ may expand the color palette for caladium plants desired by greenhouse growers, nurseries, and gardeners. This 7-page fact sheet discusses the cultivars' tuber yield potential, container trials, landscape performance, growing recommendations, and availability. Written by Zhanao Deng, and published by the UF Department of Environmental Horticulture, December 2015.